THE INFLUENCE OF WORK-LIFE BALANCE AND WORK ENVIRONMENT ON EMPLOYEE PRODUCTIVITY THROUGH JOB STRESS - Purwanto, Fajar; Pratiwi, Elok Cahyaning (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2024)
This study identifies the factors affecting employee productivity in industries undergoing relocation in Mojokerto Regency. Using a quantitative survey, data were collected from 99 respondents systematically selected from a population of 56,000 employees. Data analysis was conducted using PLS-SEM via SmartPLS to evaluate the relationships between work-life balance, work environment, job stress, and employee productivity. The results indicate that work-life balance and work environment significantly influence productivity, with job stress serving as an important mediator. Industrial relocation increases job stress, negatively impacting productivity. This study highlights the importance of stress management during the relocation process to maintain productivity. However, the study is limited by its small sample size and the specific context of relocation, which may not be universally applicable. Future research is recommended to expand the scope and consider other factors, such as managerial support and flexible work policies.